Parental Perceptions of Nondisabled Preschoolers in Inclusive Classroom Settings - Maine, Erica (East Carolina University, 2013)
The current study investigates perceptions, thoughts, and concerns of parents of nondisabled children enrolled in inclusive preschool classrooms. Utilizing a phenomenological approach and Ecological Systems theory, parents (N = 7) of nondisabled children, enrolled in an inclusive preschool classroom, were interviewed to collect the data. Results indicate that parental perspectives, thoughts, and experiences vary. While parents are supportive of inclusion in child care centers, they felt less than confident in explaining limitations of special needs to their children. Future research and development of educational programs for parents may be beneficial in increasing parental support and involvement within inclusive preschool classrooms.
Keywords: Early childhood education; Education policy; Inclusion; Preschool classroom; Inclusive education--United States; Preschool children--United States; Parent and child--United States; Parents--United States--Attitudes